Design and Development of System for Identification of Vehicle Seat Vacancy - GS, Gawande; KO, Gurbani; AN, Dolas (International Journal of Computer Sciences and Engineering, 2019)
In this proposal, face detection algorithm is developed to detect the number of faces present in a vehicle and corresponding to the detection system gives the count of the people. The images are captured using the webcam, which is installed in a vehicle and connected through a raspberry pi model B. As the vehicle leaves the station, the camera captures the images of the passenger in a seating area. The system is based on real-time application the camera will continuously capture the images and the count is also continuously modified. Then images that are captured are pre-processed via improved and adjusted to reduce the noise using software application. After pre-processing and post-processing steps are performed the images is send to the server using websocket protocol. The system obtains the maximum number of passengers in vehicle using face detection technology and thus gives the total face count of the passengers.